PETIR MENURUT AL-QUR’AN DAN ILMU PENGETAHUAN ALAM: ANALISIS PENAFSIRAN KATA AL-RA’DU, AL-BARQU, DAN AL-SHA’IQAH : (Lightning According to The Qur'an and Natural Science: Analysis of The Interpretation of The Words Al-Ra'du, Al-Barqu, and Al-Sha'iqah) - Yasser Muda Lubis; Hasan Fadli Hasibuan (Raqib: Jurnal Studi Islam, 2024)
This article discusses lightning according to the Koran and natural science. The main focus of this research is to explore the ulama's interpretation of the lightning phenomenon in the text of the Koran. The research method used is the Maudhu'i interpretation method with a scientific interpretation approach. This research is qualitative descriptive analytical, by exploring the relationship between verses from the Koran relating to lightning and natural science concepts. The research results show that there is a connection between the interpretation of lightning in the Al-Qur'an and the concept of natural science, especially in the process of lightning occurrence. The explanation presented based on a scientific approach provides a deeper understanding of the relationship between religious beliefs and scientific knowledge. From the results of this research, it can be concluded that understanding lightning in the Koran can provide a valuable contribution in enriching religious and scientific insight. Further discussion regarding the relevance of the findings of this research to the development of interpretive and natural science studies is also presented. Thus, this research provides a significant contribution in understanding the relationship between lightning from the perspective of the Koran and natural science, as well as its relevance in religious and scientific contexts.